The influence of polar (0001) zinc oxide (ZnO) on the structure and morphology of vanadyl phthalocyanine (VOPc) - Ramadan,AJ; Rochford,LA; Ryan,MP; Jones,TS; Heutz,S (RSC Advances, 2015)
Metal oxide thin films are increasingly utilized in small molecular organic photovoltaic devices to facilitate electron transport and injection. Despite this there is little understanding of the influence these layers have on the structure of adjacent organic semiconductor layers. Here we use both O- and Zn- terminated (0001) single crystal zinc oxide (ZnO) as a model system to investigate the effect of a metal oxide surface on the growth of a molecular semiconductor, vanadyl phthalocyanine (VOPc). The surface reconstructions of these model surfaces are determined and the properties of thin films of VOPc deposited atop are investigated. The nature of the bulk truncation of the surface is found to have pronounced effects on both the morphology and crystal structure of these molecular films. This work highlights the importance of considering the effects of the chemical composition and surface termination of metal oxide films on the structure of adjacent molecular semiconductor films.